Impact of probiotics on sleep quality and mood states in patients with insomnia: a systematic review and meta-analysis - Liu, Yi; Yu, Yunfeng; Lu, Shenghua; Tan, Kang; Jiang, Pengfei; Liu, Pei; Peng, Qinghua (Frontiers in Microbiology, 2025)
BackgroundProbiotics have garnered increasing attention for their potential role in managing insomnia. This meta-analysis evaluated the effects of probiotics on sleep quality and mood in patients with insomnia.MethodsEight public databases were searched to identify relevant randomized controlled trials (RCTs) published before December 2024. Data from included studies were extracted, and their risk of bias was assessed. Meta-analysis, sensitivity analysis, and publication bias assessment were conducted using Review Manager 5.3 software. The certainty of evidence was evaluated using Grading of Recommendations Assessment, Development and Evaluation (GRADE) system.ResultsSix studies, encompassing 424 patients, were included. Compared to control groups, the probiotic interventions were associated with a significant reduction in Pittsburgh Sleep Quality Index (PSQI) (mean difference [MD] −2.10, 95% confidence interval [CI] −3.86 to −0.34, p = 0.02, GRADE: moderate) and Hamilton Depression Scale (HAMD) (MD −7.72, 95% CI −14.55 to −0.89, p = 0.03, GRADE: very low) scores. However, no significant effects were observed on total sleep time (MD 43.70, 95% CI −18.07 to 105.46, p = 0.17, GRADE: very low), sleep efficiency (MD 0.41, 95% CI −1.67 to 2.48, p = 0.70, GRADE: moderate), or sleep latency (MD −4.74, 95% CI −9.42 to −0.05, p = 0.05, GRADE: moderate). Additionally, no significant differences in total adverse events were noted between probiotic and control groups. Funnel plots indicated no publication bias for PSQI, sleep efficiency, or sleep latency, whereas potential publication bias was detected for HAMD, total sleep time, and total adverse events.ConclusionProbiotic interventions improved sleep quality and reduced depressive symptoms in patients with insomnia without increasing the risk of adverse events. These findings highlight the potential of probiotics as complementary treatments for insomnia. However, due to the limited sample size, further high-quality clinical studies are warranted to confirm these findings.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251077696, identifier CRD420251077696.